Preparation, Characterization and Catalytic Test of MoVSb and MoVNb Mixed Oxide Catalyst for Propane Ammoxidation to Acrylonitrile - Ramli, Anita; Ibrahim, Suhaina M. (Asian Network for Scientific Information, 2010)
MoVSb and MoVNb mixed catalysts were prepared using reflux method for the propane ammoxidation to acrylonitrile. These catalysts were characterized using N2 physisorption (BET), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and catalytic tests. The catalytic testing shows that the MoVSbO catalyst has higher selectivity to ACN but lower conversion of propane as compared to the MoVNbO catalyst.